Collagen-chitosan composite microsphere with high biocompatibility as well as preparation method and application of collagen-chitosan composite microsphere

The collagen-chitosan composite microspheres prepared by the emulsification linkage method solves the problem of non-degradation and degradation of existing skin implants, realizes high biocompatibility and biodegradability, significantly promoting collagen regeneration And skin repair.

CN119367596APending Publication Date: 2025-01-28COLLAGEN (WUHAN) BIOTECHNOLOGY CO LTD

Patent Information

Application Number
CN202410500097.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-24
Publication Date
2025-01-28

Smart Images

  • Figure CN119367596A_ABST
    Figure CN119367596A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials, and particularly relates to a preparation method and application of collagen-chitosan composite microspheres with high biocompatibility, the collagen-chitosan composite microspheres are prepared through an emulsification cross-linking method, and the particle size is 30-50 microns; the collagen-chitosan composite microsphere disclosed by the invention has the advantages that the injectability and the degradability are good; the collagen-chitosan composite microsphere implant has high biocompatibility and biological activity, and can be used for promoting the proliferation, adhesion and migration of fibroblasts (HFF-1); the collagen-chitosan composite microspheres can effectively repair photoaging skin, improve skin elasticity and remarkably promote regeneration of collagen; the collagen-chitosan composite microspheres disclosed by the invention are mild in preparation condition, high in efficiency and short in time; the collagen-chitosan composite microsphere prepared by the method can be used in the fields of dermatology, tissue engineering and the like, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and specifically relates to a collagen-chitosan composite microsphere with high biocompatibility, a preparation method and application thereof. Background Art

[0002] Skin aging is an inevitable physiological process that leads to a decline in extracellular matrix components, inducing skin dysfunction and even causing skin cancer. Skin aging is mainly manifested by the production of fine lines and wrinkles, pigmentation, skin inflammation, and reduced skin moisture and elasticity. Collagen is the main structural protein in the dermis and provides support for the skin. Ultraviolet radiation is considered to be the main cause of skin aging, which reduces collagen synthesis and increases the secretion of matrix metalloproteinases (MMPs), leading to increased collagen degradation. Therefore, the development of effective strategies to stimulate collagen regeneration is crucial to promote skin rejuvenation.

[0003] Skin implants have the advantages of less trauma, shorter recovery time, and obvious repair effects, and are used to delay skin aging. Microsphere implants can stimulate collagen regeneration, thereby achieving tissue filling. Current microsphere implants are mostly polymer microsphere implants, mainly polymethyl methacrylate (PMMA) microspheres, polylactic acid (PLA) microspheres, etc. Patent CN10119871A discloses a PMMA microsphere implant, but PMMA microspheres are not degradable in vivo. Patent US006716251B1 discloses a PLLA microsphere implant, but its degradation process is slow, and high-concentration PLLA microspheres are prone to cause adverse reactions such as nodules and granulomas. Therefore, developing a highly biocompatible, degradable natural biomaterial microsphere implant has become a technical problem that needs to be solved urgently by those skilled in the art.

[0004] In view of the above problems, the present invention prepares a highly biocompatible collagen-chitosan composite microsphere for skin rejuvenation. The microspheres have a good size (30-50 μm), which effectively prevents the microspheres from being phagocytosed by macrophages. Collagen-chitosan composite microspheres have good injectability and biodegradability; collagen-chitosan composite microspheres have good biocompatibility and bioactivity, and effectively promote the proliferation, adhesion and migration of HFF-1 cells. After the composite microspheres are implanted into the skin of photoaged mice, the dermis density can be increased and the skin elasticity can be enhanced. After implantation, the collagen-chitosan composite microspheres are wrapped by fibroblasts, thereby stimulating collagen regeneration. Collagen-chitosan composite microspheres have a significant effect on repairing wrinkles on photoaged skin, showing great potential in the field of skin rejuvenation. Summary of the invention

[0005] In view of the above technical problems, the primary purpose of the present invention is to provide a highly biocompatible collagen-chitosan composite microsphere, wherein the collagen-chitosan composite microsphere is obtained by emulsifying and cross-linking a chitosan solution and a collagen solution in a ratio of 7:3 to 3:7.

[0006] The second object of the present invention is to provide a method for preparing the collagen-chitosan composite microspheres. The method for preparing the collagen-chitosan composite microspheres is as follows:

[0007] (1) Oil phase: Take n-hexane and liquid paraffin, add 0.02-0.08 g / mL emulsifier, and stir;

[0008] (2) Aqueous phase: chitosan solution and collagen solution are prepared at a ratio of 7:3 to 3:7;

[0009] (3) Emulsification: In a water bath, add the aqueous phase obtained in step (2) dropwise to the oil phase obtained in step (1) at an oil-water ratio of 10:1 to 4:1, stir at 400-1200 rpm, and emulsify for 6-18 min;

[0010] (4) Cross-linking: After emulsification, two cross-linking agents are added in a ratio of 1:1 to 1:4 for cross-linking;

[0011] (5) Washing: Stop stirring and wash with acetone;

[0012] (6) Centrifugation: Centrifuge in a low-temperature centrifuge and collect the precipitate.

[0013] Preferably, the ratio of n-hexane to liquid paraffin in step (1) is 0:1 to 1:0, but excluding 0:0.

[0014] Preferably, the ratio of n-hexane to liquid paraffin in step (1) is 1:1.

[0015] Preferably, the cross-linking agent in step (4) is one or more of glutaraldehyde, 1,4-butanediol diglycidyl ether, tetrahydroxymethylphosphonium chloride, carbodiimide, epichlorohydrin, sodium metaphosphate, ethylene glycol diglycidyl ether, proanthocyanidins, hesperidin, tannic acid, genipin, riboflavin, naringenin, quercetin, epigallocatechin gallate, oleuropein, L-threose, phytic acid, isocyanate, acyl azide, diphenyl phosphate, di(N-hydroxysuccinimide) suberate, vanillin, and citral.

[0016] Preferably, the cross-linking agent in step (4) is glutaraldehyde and 1,4-butanediol glycidyl ether.

[0017] Preferably, the ratio of glutaraldehyde to 1,4-butanediol glycidyl ether is 1:2.

[0018] Preferably, the emulsifier in step (1) is one or more of Tween, Span, sorbitan monooleate, sorbitan trioleate, sorbitan tristearate, sorbitan sesquioleate, glycerol ether polymer and polyoxyethylene hydrogenated castor oil.

[0019] Preferably, the emulsifier is Span 80.

[0020] Preferably, the oil-to-water ratio in step (3) is 7:1.

[0021] Preferably, the ratio of the chitosan solution to the collagen solution in step (2) is 1:1.

[0022] Preferably, the rotation speed in step (3) is 900 rpm for stirring and emulsification for 12 minutes.

[0023] Preferably, the low-temperature centrifuge in step (6) rotates at a speed of 4000 rpm for centrifugation.

[0024] The third object of the present invention is to provide the application of the collagen-chitosan composite microspheres in skin medicine and tissue engineering.

[0025] The fourth object of the present invention is to provide the use of the collagen-chitosan composite microspheres in medical and aesthetic filling materials.

[0026] The beneficial effects of the present invention are as follows: ① The present invention provides collagen-chitosan composite microspheres prepared by an emulsified double cross-linking method, with a particle size of 30-50 μm and good sphericity; ② The collagen-chitosan composite microspheres prepared by the preparation method of the present invention have good injectability and biodegradability; ③ The collagen-chitosan composite microspheres prepared by the preparation method of the present invention have high biocompatibility and can significantly promote the proliferation, adhesion and migration of fibroblasts; ④ The collagen-chitosan composite microspheres of the present invention can effectively repair photoaged skin, significantly improve skin elasticity, and restore TEWL to a normal level; ⑤ The collagen-chitosan composite microspheres of the present invention do not cause inflammatory response and can significantly promote the regeneration of collagen; ⑥ The preparation conditions of the collagen-chitosan composite microspheres of the present invention are mild, efficient and short in time; ⑦ The collagen-chitosan composite microspheres prepared by the method of the present invention can be used in the fields of skin medicine and tissue engineering, and have broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Scanning electron microscopy images of collagen-chitosan composite microspheres prepared with different cross-linking agents and cross-linking agent ratios;

[0028] Note: (A) type of cross-linking agent; (B) ratio of cross-linking agent

[0029] Figure 2 Scanning electron microscopy images of collagen-chitosan composite microspheres prepared under different conditions;

[0030] Note: (A) water phase ratio; (B) emulsification time; (C) oil-water ratio; (D) emulsifier concentration

[0031] Figure 3 Scanning electron microscopy and particle size analysis of collagen-chitosan composite microspheres prepared with different oil ratios;

[0032] Figure 4 Scanning electron microscopy and particle size analysis of collagen-chitosan composite microspheres prepared at different rotation speeds;

[0033] Figure 5 Synthesis and characterization of collagen-chitosan composite microspheres;

[0034] Note: (A) Hydroxyproline content determination; (B) Infrared spectroscopy; (C) EDS

[0035] Figure 6 Characterization diagram of the physicochemical properties of collagen-chitosan composite microspheres;

[0036] Note: (A) injection photo; (B) injectability; (C) PBS degradation; (D) pepsin degradation; (E) Col enzyme degradation

[0037] Figure 7 Biocompatibility and bioactivity of collagen-chitosan composite microspheres;

[0038] Note: (A) toxicity; (B) proliferation; (C) viable cell count; (D) live / dead cell staining; (E) adhesion; (F) migration

[0039] Figure 8 Combo evaluates the performance of collagen-chitosan composite microspheres;

[0040] Note: (A) Dermoscopy; (B) Ultrasound skin imaging; (C) Skin elasticity; (D) Transepidermal water loss

[0041] Fig. 9 Histological analysis to evaluate the bioactivity of collagen-chitosan composite microspheres;

[0042] Note: (A) H&E staining; (B) Masson staining DETAILED DESCRIPTION

[0043] The present invention is described in detail below through specific embodiments. Any technical solutions that can be conceived by any technician in the field based on the present invention and combined with the common knowledge in the field belong to the protection scope of the present invention.

[0044] Example 1. Preparation of collagen solution and chitosan solution

[0045] 1. Preparation of Collagen Solution

[0046] Medical grade yak collagen solution (concentration of 3.60 mg / mL) was prepared with reference to Chinese patent CN 112778412Α. A phosphate buffer (PB) with a concentration of 20 mM and a pH of 7.40 was prepared. The collagen solution and PB buffer were mixed in a ratio of 1:2 and incubated for 30 min. Subsequently, the obtained sediment was dispersed in 20 mM PB buffer to a final concentration of 3 mg / mL and incubated at 17 °C for 19 h. Homogenize, sieve, and collect collagen fibers by centrifugation. Subsequently, the collagen fibers were dispersed in a PBS solution to a final concentration of 3 mg / mL.

[0047] 2. Preparation of Chitosan Solution

[0048] 240 mg of chitosan was placed in 80 mL of 0.10 M acetic acid and stirred to dissolve it until it became colorless and transparent, thereby obtaining a 3 mg / mL chitosan solution.

[0049] Example 2: Preparation of collagen-chitosan composite microspheres

[0050] 1. Preparation of collagen-chitosan composite microspheres with different crosslinking agents

[0051] Mix 35 mL of n-hexane and 35 mL of liquid paraffin to make 70 mL of oil phase. Add 2.80 g of Span 80 to the oil phase and stir for 5 minutes. Then, use 5 mL of collagen solution and 5 mL of chitosan solution as the aqueous phase at the same time. Add the aqueous phase dropwise to the oil phase containing Span 80, and emulsify at a speed of 900 rpm for 12 minutes. After emulsification, add 0.5 mL of GA, 0.5 mL of BDDE, and 0.5 mL of citral to the reaction system without adding a crosslinker. After stirring for 1 hour, wash with acetone. Centrifuge at 4000 rpm in a low-temperature centrifuge, collect the precipitate, and obtain collagen-chitosan composite microspheres cross-linked by different crosslinkers.

[0052] Scanning electron microscopy images of collagen-chitosan composite microspheres prepared by cross-linking with different cross-linking agents ( Figure 1 A), the results show that when there is no crosslinking agent, it is difficult to form microspheres and they are irregular in shape. When the crosslinking agent is BDDE, the microspheres have poor sphericity and are in uneven blocks. When the crosslinking agent is GA, the prepared microspheres have good sphericity, uniform particle size and smooth surface. However, when the crosslinking agent is citral, spheres cannot be formed. The results show that the crosslinking agent has a significant effect on the morphology of collagen-chitosan composite microspheres.

[0053] 2. Preparation of collagen-chitosan composite microspheres with different crosslinking agent ratios

[0054] 35 mL of n-hexane and 35 mL of liquid paraffin were mixed to prepare 70 mL of oil phase. 2.80 g of Span80 was added to the oil phase and stirred for 5 min. Then, 5 mL of collagen solution and 5 mL of chitosan solution were used as the aqueous phase. The aqueous phase was added dropwise to the oil phase containing Span 80, and emulsified at a speed of 900 rpm for 12 min. After emulsification, 1000 μL of cross-linking agent (GA: BDDE = 1: 1), 750 μL of cross-linking agent (GA: BDDE = 1: 2), 660 μL of cross-linking agent (GA: BDDE = 1: 3), and 625 μL of cross-linking agent (GA: BDDE = 1: 4) were added to the reaction system respectively. After stirring for 1 h, acetone was used for washing. Centrifuge at 4000 rpm in a low-temperature centrifuge, collect the precipitate, and obtain collagen-chitosan composite microspheres cross-linked with different cross-linking agent dosage ratios.

[0055] Scanning electron microscopy images of collagen-chitosan composite microspheres prepared with different crosslinking agent dosages ( Figure 1 B), when GA:BDDE is 1:1, the microspheres have good sphericity and most of them are spherical; when GA:BDDE is 1:2, the microspheres have good sphericity and most of them are spherical; when GA:BDDE is 1:3, the microspheres have poor sphericity and some of them have irregular shapes; when GA:BDDE is 1:4, the microspheres have worse sphericity and the proportion of irregular shapes increases significantly. The results show that by adjusting the dosage ratio of BDDE to GA, collagen-chitosan composite microspheres with good sphericity and uniformity can be prepared.

[0056] 3. Preparation of collagen-chitosan composite microspheres with different proportions of aqueous phase

[0057] Mix 35 mL of n-hexane and 35 mL of liquid paraffin to make 70 mL of oil phase. Add 2.80 g of Span 80 and stir for 5 min. The ratios of collagen:chitosan (v / v) in the aqueous phase are 7:3, 5:5, and 3:7, respectively. Add the aqueous phase dropwise to the oil phase containing Span 80 and emulsify at a speed of 900 rpm for 12 min. After emulsification, add 0.25 mL of GA and 0.50 mL of BDDE to the reaction system, stop stirring after stirring for 1 h, and let stand. Wash with acetone, centrifuge at 4000 rpm in a low-temperature centrifuge, collect the precipitate, and obtain collagen-chitosan composite microspheres prepared with different proportions of aqueous phase.

[0058] Scanning electron microscopy of collagen-chitosan composite microspheres prepared with different aqueous phases ( Figure 2A) shows that the spheroidization of collagen-chitosan composite microspheres prepared under the conditions of collagen:chitosan (v / v) in the aqueous phase of 7:3, 5:5, and 3:7 is different. When the ratio of collagen to chitosan is 7:3, the spheroidization of collagen-chitosan composite microspheres is better. When the ratio of collagen to chitosan is 5:5, the spheroidization of collagen-chitosan composite microspheres is significantly improved. When the ratio of collagen to chitosan is 3:7, the collagen-chitosan composite microspheres still maintain a good spherical morphology. The results show that the spheroidization of collagen-chitosan composite microspheres can be regulated by adjusting the ratio of collagen to chitosan in the aqueous phase.

[0059] 4. Preparation of collagen-chitosan composite microspheres at different emulsification times

[0060] 35 mL of n-hexane and 35 mL of liquid paraffin were mixed to prepare 70 mL of oil phase. 2.80 g of Span 80 was added and stirred for 5 min. Then, 5 mL of collagen solution and 5 mL of chitosan solution were added as the aqueous phase at the same time. The aqueous phase was added dropwise to the oil phase containing Span 80 and emulsified at a speed of 900 rpm. The emulsification time was 6, 12, and 18 min, respectively. After emulsification, 0.25 mL of GA and 0.50 mL of BDDE were added to the reaction system for cross-linking. After stirring for 1 h, acetone was used for washing. Centrifuge at a low temperature centrifuge of 4000 rpm, collect the precipitate, and obtain collagen-chitosan composite microspheres prepared with different emulsification times.

[0061] Scanning electron microscopy and particle size analysis of collagen-chitosan composite microspheres prepared at different emulsification times ( Figure 2 B), when emulsified for 6 minutes, the sphericity of the microspheres was poor and the particle size was uneven. With the increase of the emulsification time, the collagen-chitosan composite microspheres prepared by emulsification for 12 minutes were regular in spherical shape and uniformly dispersed. However, the emulsification time was too long (emulsification for 18 minutes), resulting in poor sphericity of the microspheres and uneven particle size. The results show that when the emulsification time is 12 minutes, the sphericity and dispersibility of the microspheres are good.

[0062] 5. Preparation of collagen-chitosan composite microspheres with different oil-water ratios

[0063] Mix 35mL of n-hexane and 35mL of liquid paraffin to prepare 70mL of oil phase. Add 2.80g of Span80 to the oil phase and stir for 5min. Prepare 17.50mL, 10mL and 7mL of collagen solution and chitosan solution (v / v=1 / 1) as the aqueous phase. Add the aqueous phase dropwise to the oil phase containing Span 80 and emulsify at 900rpm for 12min. After emulsification, add 0.25mL of GA and 0.50mL of BDDE to the reaction system for cross-linking. After stirring for 1h, stop stirring and let stand. Wash with acetone, then centrifuge at 4000rpm in a low-temperature centrifuge, collect the precipitate, and obtain collagen-chitosan composite microspheres with different oil-water ratios.

[0064] Scanning electron microscopy images and particle size analysis of collagen-chitosan composite microspheres prepared with different oil-water ratios ( Figure 2 C), the results show that the microspheres are in a state of agglomeration when the oil-water ratio is 4:1. When the oil-water ratio is 10:1, the dispersibility of the microspheres is improved, but the average particle size (22.51μm) is small. When the oil-water ratio is 7:1, the average particle size (30μm) of the microspheres prepared is suitable for injection, with high sphericity and good dispersibility.

[0065] 6. Preparation of collagen-chitosan composite microspheres with different emulsifier dosages

[0066] 35mL of n-hexane and 35mL of liquid paraffin were mixed to prepare 70mL of oil phase. 2.80g of Span 80 was added and stirred for 5min. Then, 5mL of collagen solution and 5mL of chitosan solution were added as the aqueous phase at the same time. The aqueous phase was added dropwise to the oil phase containing different amounts of Span 80 (0.02mg / mL, 0.04mg / mL, 0.08mg / mL), and the speed was emulsified at 900rpm for 12min. After the emulsification was completed, 0.25mL of GA and 0.50mL of BDDE were added to the reaction system and stirred for 1h, and then washed with acetone. Then, centrifuged at a low temperature centrifuge of 4000rpm, and the precipitate was collected to obtain collagen-chitosan composite microspheres prepared with different speeds.

[0067] Scanning electron microscopy and particle size analysis of collagen-chitosan composite microspheres prepared with different emulsifier addition amounts ( Figure 2 D), the results show that when the emulsifier concentration is 0.02mg / mL, the microspheres have good sphericity, but are relatively agglomerated with a particle size of 29.35μm. When the emulsifier concentration is 0.04mg / mL, the microspheres are uniform and well dispersed, with a particle size of 30μm. When the emulsifier concentration is 0.08mg / mL, the microspheres are slightly agglomerated, with a particle size of 30.72μm.

[0068] 7. Preparation of collagen-chitosan composite microspheres by comparing different oils

[0069] 70 mL of oil phase was prepared by mixing liquid paraffin and n-hexane in a ratio of 1:0, 0:1, 1:1, 1:2, and 2:1. 2.80 g of Span 80 was added to the oil phase and stirred for 5 min. Next, 5 mL of collagen solution and 5 mL of chitosan solution were added at the same time as the aqueous phase. The aqueous phase was added dropwise to the oil phase containing Span 80, and emulsified at a speed of 900 rpm for 12 min. After emulsification, 0.25 mL of GA and 0.50 mL of BDDE were added to the reaction system and stirred for 1 h, washed with acetone, and the precipitate was collected by centrifugation at a low temperature centrifuge at 4000 rpm to obtain collagen-chitosan composite microspheres with different oil phase ratios.

[0070] Scanning electron microscopy and particle size analysis of collagen-chitosan composite microspheres prepared with different oil ratios ( Figure 3 ), the particle sizes of microspheres prepared by different oil-water liquid paraffin and n-hexane at 1:0, 2:1, 1:1, 1:2, 0:1 were 3.37μm, 21.18μm, 33.21μm, 35.06μm, 47.65μm respectively; the proportions of microspheres with particle sizes of 30-50μm were 0%, 6.73%, 91.22%, 73.92%, 45.29% respectively. The results show that the particle size of microspheres increases with the increase of n-hexane dosage, and the sphericity and dispersibility of microspheres are good when the ratio is 1:1.

[0071] 8. Preparation of collagen-chitosan composite microspheres at different rotation speeds

[0072] 35mL of normal hexane and 35mL of liquid paraffin are mixed to make 70mL of oil phase. 2.80g of Span 80 is added and stirred for 5min. Then, 5mL of collagen solution and 5mL of chitosan solution are added as aqueous phase at the same time. The aqueous phase is added dropwise to the oil phase containing Span 80, and emulsified at different speeds (400rpm, 600rpm, 900rpm, 1200rpm) for 12min. After emulsification is completed, 0.25mL of GA and 0.50mL of BDDE are added to the reaction system and stirred for 1h, and then washed with acetone. Then, centrifuged under a low-temperature centrifuge at 4000rpm, the precipitate is collected to obtain collagen-chitosan composite microspheres prepared at different speeds.

[0073] Scanning electron microscopy and particle size analysis of collagen-chitosan composite microspheres prepared at different rotation speeds ( Figure 4), the particle sizes of the microspheres prepared at the speeds of 400rpm, 600rpm, 900rpm, and 1200rpm were 53.47μm, 41.75μm, 36.24μm, and 24.31μm, respectively; the proportions of microspheres with a particle size of 30-50μm were 42.86%, 68.54, 90.77%, and 15.11%, respectively. The results showed that the particle size of the microspheres decreased with the increase of the speed. When the speed was 900rpm, the microspheres had better sphericity and uniform particle size, which was suitable for injection.

[0074] Comparative Example 1: Preparation of collagen microparticles

[0075] 70 mL of oil phase was prepared by mixing n-hexane and liquid paraffin in a volume ratio of 1:1. Then 2.80 g of Span 80 was added and stirred for 5 min. 10 mL of collagen solution was used as the aqueous phase, and the aqueous phase was added dropwise to the oil phase containing Span 80, and emulsified at a speed of 900 rpm for 12 min. After emulsification, 0.25 mL of GA and 0.50 mL of BDDE were added to the reaction system for cross-linking. After stirring for 1 h, it was washed with acetone. Centrifuged at 4000 rpm in a low-temperature centrifuge, and the precipitate was finally collected to obtain collagen microparticles.

[0076] Comparative Example 2: Preparation of Chitosan Microspheres

[0077] 70 mL of oil phase was prepared by mixing n-hexane and liquid paraffin in a volume ratio of 1:1. Then 2.80 g of Span 80 was added and stirred for 5 min. Subsequently, 10 mL of chitosan solution was used as the aqueous phase, and the aqueous phase was added dropwise to the oil phase containing Span 80, and emulsified at a speed of 900 rpm for 12 min. After emulsification, 0.25 mL of GA and 0.50 mL of BDDE were added to the reaction system for cross-linking. After stirring for 1 h, acetone was used for washing. Centrifuge at 4000 rpm in a low-temperature centrifuge, collect the precipitate, and finally obtain chitosan microspheres.

[0078] Comparative Example 3: Preparation of collagen-chitosan single cross-linked microspheres

[0079] 70 mL of oil phase was prepared by mixing n-hexane and liquid paraffin in a volume ratio of 1:1. Then 2.80 g of Span80 was added and stirred for 5 min. Subsequently, 5 mL of collagen solution and 5 mL of chitosan solution were used as the aqueous phase. The aqueous phase was added dropwise to the oil phase containing Span 80, and emulsified at a speed of 900 rpm for 12 min. After emulsification, 0.50 mL of GA was added to the reaction system for cross-linking. After stirring for 1 h, acetone was used for washing. Centrifuge at 4000 rpm in a low-temperature centrifuge, collect the precipitate, and finally obtain collagen-chitosan single cross-linked microspheres.

[0080] Example 3. Preparation and characterization of collagen-chitosan composite microspheres

[0081] After optimizing the factors of different cross-linking agent types, different cross-linking agent dosages, different aqueous phases, different emulsification times, different oil-water ratios, different emulsifier concentrations, different oil phases, and different rotation speeds, we finally chose to make 70 mL of oil phase with n-hexane and liquid paraffin in a volume ratio of 1:1. Then 2.80 g of Span 80 was added and stirred for 5 min. Then 5 mL of collagen solution and 5 mL of chitosan solution were used as the aqueous phase. The aqueous phase was added dropwise to the oil phase containing Span 80, and emulsified at a speed of 900 rpm for 12 min. After emulsification, 0.25 mL of GA and 0.50 mL of BDDE were added to the reaction system. After stirring for 1 h, it was washed with acetone. Centrifuged at 4000 rpm in a low-temperature centrifuge, the precipitate was collected, and finally collagen-chitosan composite microspheres were obtained.

[0082] 1. Characterization of Hydroxyproline Content in Collagen-Chitosan Composite Microsphere Implants

[0083] Take 10 mg of Comparative Example 1 (collagen microparticles), Comparative Example 2 (chitosan microspheres) and Example 3 (collagen-chitosan composite microspheres), add 1 mL of 12M concentrated hydrochloric acid to each, and place in a reactor for reaction at 105°C for 24 hours. After the reaction, take the liquid out of the reactor and adjust the pH to 7. The hydroxyproline content is determined using the chloramine T method. Hydroxyproline reacts with p-dimethylaminobenzaldehyde to form a red compound. The absorbance is measured at 561 nm to quantify the hydroxyproline content.

[0084] Determination of collagen content in collagen-chitosan composite microspheres by hydroxyproline Figure 5 A). The content of hydroxyproline in the composite microspheres was 1.45 μg / mL, the content of hydroxyproline in collagen was 2.00 μg / mL, and the proportion of collagen in the composite microspheres was 72.50%. The results showed that collagen and chitosan were successfully composited.

[0085] 2. Fourier transform infrared spectroscopy (FTIR) characterization of collagen-chitosan composite microsphere implants

[0086] Weigh 1 mg of chitosan powder, collagen sample and collagen-chitosan composite microspheres respectively, and mix them with 100 mg of dry KBr. Use a flat tablet press to compact the slices. -1 The samples were characterized by FTIR in a wide range of wavenumbers.

[0087] The infrared spectrum of collagen-chitosan composite microspheres was analyzed ( Figure 5 B) The characteristic peak of chitosan is 1404cm -1 (-CH 2 )、2878cm -1 (CH), the characteristic peak of collagen is 1656cm -1 (Amide I band, 1560 cm -1 (amide II band) and 1236 cm -1 (Amide III band). A new band of 1647 cm was added in collagen-chitosan composite microspheres. -1 (OC=NH), 1053cm -1 (-COC). The results showed that collagen-chitosan composite microspheres were successfully prepared.

[0088] 3. SEM scanning electron microscope energy dispersive spectrometry (EDS) of collagen-chitosan composite microsphere implants

[0089] The type and content of elements in collagen-chitosan composite microspheres were studied by EDS characterization. Conductive tape was attached to the sample holder, and then the microsphere powder was fixed on the conductive tape, and other loosely attached particles were removed with an ear-cleaning ball, and AuPd was sputtered for 15s before imaging.

[0090] The results showed that collagen microparticles contained C, O, and N, accounting for 26.44%, 64.43%, and 12.13% respectively. Chitosan microspheres contained C and O, accounting for 56.99% and 43.01% respectively. Collagen-chitosan double cross-linked microspheres contained C, O, and N, accounting for 45.51%, 42.83%, and 8.63% respectively. Figure 5 C). The proportion of collagen in the collagen-chitosan composite microspheres was 71.15%. The results showed that collagen and chitosan were successfully composited.

[0091] 4. Characterization of the physical and chemical properties of collagen-chitosan composite microspheres

[0092] In order to study the injectability of collagen-chitosan composite microspheres, a pushing force test was performed on them. 30 mg of Example 3 was dispersed in 1 mL of PBS, loaded into a sterile syringe, and a pushing force test was performed at a constant extrusion speed of 30 mm / min.

[0093] The results showed that collagen-chitosan double cross-linked microspheres can be continuously extruded through a syringe and injected into precise shapes during the injection process ( Figure 6 A), such as the shape of LZU or whale. The injectability of collagen-chitosan double cross-linked microspheres was further evaluated by the push force test ( Figure 6B). The average extrusion force of collagen microparticles is 2.17 N, the average extrusion force of chitosan microspheres is 1.69 N, and the average extrusion force of Example 3 is 0.90 N. The results show that collagen-chitosan composite microspheres have good injectability.

[0094] 10 mg of collagen-chitosan composite microspheres were weighed and immersed in 1 mL of phosphate buffered saline (0.01 M PBS, pH 7.0-7.2) solution, type I collagenase solution (5 U) and pepsin solution (3 mg / mL). After 1, 4 and 7 days of enzymatic hydrolysis, the samples were subjected to a series of treatments, including washing, centrifugation, freeze-drying and re-weighing, and the degradation percentage was calculated to evaluate the biodegradability of collagen-chitosan composite microspheres.

[0095]

[0096] Wherein AW%: degradation percentage; W 0 : initial weight; W: weight of the sample after enzymatic hydrolysis.

[0097] In order to study the biodegradability of collagen-chitosan composite microspheres, degradation experiments were carried out under different conditions ( Figure 6 (CE)). The degradation process was carried out in a solution containing type I collagenase (5U) and pepsin (3mg / mL) for 1, 4 and 7 days. Under PBS conditions, the degradation rates of collagen-chitosan double cross-linked microspheres were 13.08%, 28.44% and 35.45%, respectively. Under pepsin conditions, the degradation rates of collagen-chitosan double cross-linked microspheres were 15.62%, 34.04% and 43.43%. Under type I collagenase conditions, the degradation rates of collagen-chitosan double cross-linked microspheres at 1, 4 and 7 days were 23.22%, 31.68% and 43.82% at 1, 4 and 7 days, respectively. The results showed that collagen-chitosan double cross-linked microspheres have good degradability and are a degradable biomaterial.

[0098] Example 4. Cytocompatibility and cell activity of collagen-chitosan composite microspheres

[0099] 1. Toxicity

[0100] In order to study the biocompatibility of collagen-chitosan composite microspheres, cytotoxicity experiments were performed. Human foreskin fibroblast-1 (HFF-1) cells were cultured in high-glucose DMEM medium supplemented with 10% (v / v) fetal bovine serum and 1% (v / v) penicillin-streptomycin at 37°C and 5% CO. 2The cytotoxicity of the microspheres of Example 3 was studied by culturing. The microspheres of Example 3 were immersed in a high-glucose DMEM medium at 37°C for 72 hours to obtain a sample extract. Subsequently, the cells were treated with 0.25% (w / w) trypsin at a concentration of 1×10 4 The cells were seeded in 96-well plates at a density of 1.5 × 10 μl. 2 After incubation in the incubator for 24 hours, samples of different concentrations (0.10 mg / mL, 0.25 mg / mL, 0.50 mg / mL, 0.75 mg / mL, 1.00 mg / mL) were added to their respective wells and incubated for 24 hours. Then 10 μL of CCK-8 was added and incubated at 37°C for 1-3 hours. The basal culture medium was used as a blank control, and the absorbance at 450 nm was measured using a multifunctional microplate reader. The cell viability calculation formula is as follows:

[0101]

[0102] Among them, A represents the OD value of the sample, B represents the OD value of the blank control, and C represents the OD value of the culture medium.

[0103] The experimental results are as follows Figure 7 As shown in A, when the concentration is 0.10mg / mL, 0.25mg / mL, 0.50mg / mL, 0.75mg / mL,

[0104] At 1.00 mg / mL, the cell survival rates were 104.49%, 105.75%, 103.85%, 104.04% and 101.99%, respectively. The results showed that collagen-chitosan composite microspheres had no cytotoxicity and had good biocompatibility.

[0105] 2. Proliferation

[0106] The cell activity of collagen-chitosan composite microspheres was evaluated by cell proliferation assay. 4 The cells were inoculated into a 96-well plate at a density of 1.5 μg / mL. After incubation at 37°C for 24 h, the extracts (0.25 mg / mL) of the microspheres of Comparative Example 2, Comparative Example 3 and Example 3 were added to the corresponding wells and incubated for 1 d, 3 d, and 5 d, respectively. Finally, 10 μL of CCK-8 was added and incubated at 37°C for 1-3 h, and the cell proliferation rate was calculated.

[0107] The results are as follows Figure 7As shown in B, after 1d, 3d, and 5d of cell incubation, the cell survival rates of the chitosan microsphere group were 104.82%, 99.85%, and 98.91%, respectively. The cell survival rates of the collagen-chitosan single cross-linked microsphere group were 106.21%, 106.84%, and 108.65%, respectively. The cell survival rates of the collagen-chitosan composite microsphere group were 107.77%, 110.08%, and 118.25%, respectively. The results show that after reducing the amount of cross-linking agent glutaraldehyde, the collagen-chitosan composite microsphere can significantly stimulate the proliferation of HFF-1 cells and has good biocompatibility.

[0108] 3. CA / PI staining

[0109] The effect of collagen-chitosan composite microspheres on cell viability was studied by CA / PI staining. First, HFF-1 cells were treated with trypsin and plated at 2×10 4 The density of cells was inoculated in a laser confocal culture dish. After incubation at 37°C for 24 h, the extracts (100 μL) of Comparative Example 2, Comparative Example 3 and Example 3 were added to different sample wells, and 100 μL of cell culture medium was added to the blank wells. The cells were incubated for 1 and 3 days, respectively. Subsequently, the cells were stained with CA / PI and then imaged with a laser confocal microscope.

[0110] CA / PI staining results are as follows Figure 7 As shown in D, compared with the blank group, the chitosan microsphere group, the collagen-chitosan single cross-linked microsphere group, and the collagen-chitosan double cross-linked microsphere group were dominated by green fluorescent cells on the first day; on the third day, the number of live cells in the chitosan microsphere group decreased, while the number of live cells in the collagen-chitosan single cross-linked microsphere group and the collagen-chitosan double cross-linked microsphere group increased, and the increase in the collagen-chitosan double cross-linked microsphere group was more significant. The number of live cells was quantified ( Figure 7 C), the number of surviving cells in the chitosan microsphere group at 1 day and 3 days was 82 and 74; the number of surviving cells in the collagen-chitosan single cross-linked microsphere group at 1 day and 3 days was 97 and 105; the number of surviving cells in the collagen-chitosan double cross-linked microsphere group at 1d and 3d was 110 and 127. The results show that collagen-chitosan composite microspheres can effectively promote cell proliferation and have good biocompatibility.

[0111] 4. Cell Adhesion

[0112] The cell adhesion of collagen-chitosan composite microspheres was observed using an inverted fluorescence microscope. 500 μL of sample extracts (0.25 mg / mL) and denatured bovine serum albumin (BSA 0.25 mg / mL) from Comparative Example 2, Comparative Example 3, and Example 3 were added to an untreated 24-well plate. The plate was then incubated at 4°C in the dark for 24 h for adsorption. The supernatant was taken and a density of 1×10 5 500 μL of HFF-1 cell suspension (100 cells / mL) was incubated at 37°C with 5% CO 2 After incubation, the cells were observed for 6 h under an inverted microscope.

[0113] Fluorescence microscopy was used to observe the cell adhesion of collagen-chitosan composite microspheres ( Figure 7 E). HFF-1 cells were inoculated on BSA, chitosan microspheres, collagen-chitosan single cross-linked microspheres, and collagen-chitosan double cross-linked microspheres substrates, respectively. The HFF-1 cells on the BSA substrate showed a spherical structure, indicating that BSA did not have cell adhesion ability. Some HFF-1 cells on the chitosan microsphere substrate were also spherical, and the cells on the collagen-chitosan single cross-linked microsphere substrate were spindle-shaped, indicating that cell adhesion was enhanced, while on the collagen-chitosan double cross-linked microsphere substrate, most of the cells showed a spindle-shaped morphology, and the number of adhered cells increased significantly. The results show that the collagen-chitosan composite microspheres provide an environment with high biological activity for the adhesion of HFF-1 cells.

[0114] 5. Cell Migration

[0115] The cell migration of collagen-chitosan composite microspheres was observed using an inverted fluorescence microscope. Three horizontal lines were drawn on the bottom of the 6-well plate with a marker pen, with a spacing of 0.50-1.00 cm. HFF-1 cells were digested with 0.25% (w / w) trypsin and the density of each well was 1×10 6 The cells were inoculated in a culture dish and incubated at 37°C for 24h until the bottom of the plate was completely covered. Subsequently, a 10μL pipette tip was used to create cell scratches vertically along the bottom horizontal line to form a scratch area. Then rinse three times with PBS to remove the detached cells. 2mL of each of the extracts of Comparative Example 2, Comparative Example 3 and Example 3 and high-glucose DMEM medium were added to the wells of a 6-well plate and incubated at 37°C. The plate was removed at 0h and 24h, and an inverted microscope was used to capture images of the scratch area. The migration of cells was determined by measuring the migration distance. The formula for calculating cell migration rate is as follows:

[0116]

[0117] Where L 0 is the intercellular gap width at 0h, L t is the intercellular gap width at 24 h.

[0118] The experimental results are as follows Figure 7 As shown in F, chitosan microspheres, collagen-chitosan single cross-linked microspheres and collagen-chitosan double cross-linked extracts were co-cultured with cell culture medium and HFF-1 cells for 24 hours, and the migration rate of cells was evaluated. The cell migration rate of the blank group was 3.12%, the cell migration rate of the chitosan microsphere group was 19.62%, the cell migration rate of the collagen-chitosan single cross-linked microsphere group was 35.29%, and the cell migration rate of the collagen-chitosan double cross-linked microsphere group was 45.45%. The results showed that collagen-chitosan composite microspheres significantly enhanced the migration ability of HFF-1 cells.

[0119] Example 5: Animal Experiment

[0120] 1. Construction of Photoaging Mouse Model

[0121] Animal experiments were conducted in accordance with the ethical standards of the Ethics Committee of the School of Chemistry and Chemical Engineering of Lanzhou University. Thirty male Kunming mice aged 6-8 weeks were purchased at the Lanzhou Animal Experiment Center. Before the start of the experiment, the dorsal region of the mice was shaved and they were placed in custom-made cages with protective eye masks. A total of 30 mice were assigned to 6 groups, each consisting of 6 mice: blank group, control group, comparative example group 2, comparative example group 3, and example group 3. The blank group consisted of normal mice and did not receive any specific treatment. The control group consisted of mice exposed to UV irradiation and did not receive any injection. Comparative example group 2, comparative example group 3, and example group 3, which were also exposed to UV irradiation, were injected with 100 μL of chitosan microspheres, collagen-chitosan single-crosslinked microspheres, and collagen-chitosan double-crosslinked microsphere implants dispersed in PBS at a concentration of 30 mg / mL.

[0122] The exposed skin of mice was irradiated with UVA and UVB lamps at a distance of 30 cm. Preliminary experiments determined that the minimum erythema dose (MED) value was UVA 0.29 J / cm 2 , UVB 6.71mJ / cm 2 . To construct a UV-induced photoaging skin model, mice were subjected to three stages of UV irradiation. In the first stage, which lasted for 2 weeks, mice were irradiated every day under MED conditions. In the second stage, which lasted for 2 weeks, the irradiation dose was increased to twice the MED every other day. The third stage lasted for 4 weeks, during which the mice were irradiated with 3 times the MED every other day. The entire irradiation cycle was 8 weeks, and the cumulative UVA irradiation dose was 20.30 J / cm 2 The cumulative UVB dose is 0.47 J / cm 2Before irradiation, excess hair was removed and 100 μL of samples from different groups were injected subcutaneously into the exposed skin of mice in the treatment group. At the end of the 8th week, mice were euthanized using an overdose of sodium pentobarbital and skin samples were collected from the implantation site.

[0123] 2.Combo evaluation of mouse skin condition

[0124] To gain a more comprehensive understanding of the appearance of mouse skin, Combo dermoscopy was performed. Specific measurement points were selected on the back skin, and 3 measurements were performed at each measurement point. Images were acquired by pressing the "Freeze" button on the screen, and the system automatically saved the images. Skin density was determined using Combo ultrasound skin imaging. Before each ultrasound scan, a small amount of gel, deionized water, or distilled water should be applied to the front end of the probe. The probe was then placed on the skin area to be scanned for scanning. Skin elasticity was evaluated using the elasticity measurement function of the Combo system. Before measurement, ensure that the skin surface is clean and dry, place the probe on the skin, and then measure. The transepidermal water loss (TEWL) probe of the Combo system was used to evaluate the repair ability of collagen-chitosan composite microspheres on transepidermal water loss of the skin, and the probe was placed on the skin for measurement.

[0125] Combo dermatoscope was used to examine the appearance of mouse skin ( Figure 8 A). The skin of the blank group showed no wrinkles, the skin of the control group showed obvious and deepened wrinkles, the skin of the chitosan microsphere group showed shallow wrinkles, the wrinkles of the collagen-chitosan single cross-linked microsphere group were not obvious, and the skin of the collagen-chitosan double cross-linked microsphere group was wrinkle-free. The results show that collagen-chitosan composite microspheres can effectively repair photoaged skin.

[0126] Combo ultrasound imaging was used to evaluate the repair ability of collagen-chitosan composite microsphere implants on photoaged mouse skin. Figure 8 B). Compared with the control group, the yellow area of ​​the chitosan microsphere group increased slightly, the white and yellow areas of the collagen-chitosan single cross-linked microsphere group increased significantly, and the green area of ​​the collagen-chitosan double cross-linked microsphere group decreased, and the white and yellow areas increased significantly, indicating that the dermal density increased significantly. The results show that collagen-chitosan composite microsphere implants can increase the dermal density of the skin and repair skin aging.

[0127] Evaluation of the restoration of photoaged skin by collagen-chitosan composite microsphere implants by measuring skin elasticity ( Figure 8C). The skin elasticity value of the blank group was 2.23. Compared with the blank group, the skin elasticity of the control group mice decreased by 47.08%, and the elasticity value was 1.18, indicating that ultraviolet irradiation had a significant effect on the skin condition of mice. Compared with the control group, the skin elasticity of the chitosan microsphere group increased by 20.33%, the skin elasticity of the collagen-chitosan single cross-linked group increased by 29.66%, and the skin elasticity of the collagen-chitosan composite microsphere group increased by 87.28%, which were 1.42, 1.53, and 2.21, respectively. The results showed that the collagen-chitosan composite microsphere implant can significantly restore the elasticity of photoaged skin.

[0128] Evaluation of the repair effect of collagen-chitosan composite microsphere implants on aged skin by measuring transepidermal water loss ( Figure 8 D). TEWL represents the loss of water from the dermis through epidermal evaporation, and higher values ​​indicate increased water loss from the skin and impaired skin barrier function. Compared with the blank group (9.11), the TEWL of the control group (43.69) increased by 379.58%, indicating that UV exposure destroyed the integrity of the skin barrier. Compared with the control group, the TEWL of the chitosan microspheres, collagen-chitosan single-crosslinked microspheres, and collagen-chitosan double-crosslinked groups decreased by 72.14% (12.17), 74.14% (11.30), and 78.85% (9.24), respectively. The results showed that collagen-chitosan composite microsphere implants helped to restore the TEWL value of photoaged skin to near normal levels.

[0129] 3. Histological Evaluation of Implant Performance

[0130] The degree of inflammation in the mouse skin tissue was observed by hematoxylin-eosin (H&E) staining. The mice were euthanized by an overdose of sodium pentobarbital at 8 weeks, and skin samples were collected from the implantation site. The skin samples were then embedded in paraffin, and then paraffin sections were made for H&E staining.

[0131] Evaluation of the inflammatory response to collagen-chitosan composite microsphere implants by H&E staining ( Fig. 9 A). No inflammatory reaction was observed in the blank group. After 8 weeks of implantation, obvious inflammatory cell infiltration was observed in the control group. More inflammatory cells appeared in the chitosan microsphere group, fewer inflammatory cells appeared in the collagen-chitosan single cross-linked microsphere group, and a small number of inflammatory cells were present around the collagen-chitosan composite microsphere group. Fibroblasts grew around the microspheres. During the entire observation period, no foreign body granuloma reaction was observed around the collagen double cross-linked composite microsphere group. The results showed that the collagen double cross-linked composite microspheres did not cause inflammatory reaction after 8 weeks of implantation.

[0132] The ability of collagen-chitosan composite microsphere implants to promote collagen regeneration was evaluated by Masson's trichrome staining of mouse skin tissue. At week 8, mice were euthanized using an overdose of sodium pentobarbital, and skin specimens were collected from the implantation site. Paraffin sections were then made and Masson's trichrome stained.

[0133] Masson trichrome staining was performed on the skin tissue to further study the formation of collagen fibers after implantation of collagen-chitosan composite microspheres ( Fig. 9 B). An increase in collagen fibers was observed in the blank group, while the control group showed a decrease and breakage of collagen fibers. Compared with the control group, the chitosan microspheres showed a slight increase in collagen fibers around the microspheres, the collagen-chitosan single cross-linked microspheres group showed a small increase in collagen fibers at the implantation site, and the newly formed collagen fibers in the collagen-chitosan double cross-linked microspheres group were denser. The results showed that collagen-chitosan composite microspheres can significantly promote the regeneration of collagen and accelerate the skin remodeling process.

[0134] In summary, ① the present invention provides collagen-chitosan composite microspheres prepared by an emulsification crosslinking method, with a particle size of 30-50 μm and good sphericity; ② the collagen-chitosan composite microspheres prepared by the preparation method of the present invention have good injectability and biodegradability; ③ in addition, the composite microspheres also have high biocompatibility and can significantly promote the proliferation, adhesion and migration of fibroblasts; ④ the collagen-chitosan composite microspheres of the present invention can effectively repair photoaged skin, significantly restore the elasticity of photoaged skin, and restore the TEWL value of photoaged skin to a level close to normal; ⑤ the collagen-chitosan composite microspheres of the present invention will not cause inflammatory response, can significantly promote the regeneration of collagen, and accelerate the skin remodeling process; ⑥ the preparation conditions of the collagen-chitosan composite microspheres of the present invention are mild, efficient and short in time; ⑦ the collagen-chitosan composite microspheres prepared by the method of the present invention can be used in the fields of skin medicine and tissue engineering, and have broad application prospects.

Claims

1. A highly biocompatible collagen-chitosan composite microsphere, characterized in that: The collagen-chitosan composite microspheres are obtained by emulsifying and cross-linking a chitosan solution and a collagen solution in a ratio of 7:3-3:

7.

2. The method for preparing collagen-chitosan composite microspheres according to claim 1, characterized in that: The preparation method of the collagen-chitosan composite microspheres is as follows: (1) Oil phase: Take n-hexane and liquid paraffin, add 0.02-0.08 g / mL emulsifier, and stir; (2) Aqueous phase: chitosan solution and collagen solution were prepared at a ratio of 7:3-3:7; (3) Emulsification: In a water bath, add the aqueous phase obtained in step (2) dropwise to the oil phase obtained in step (1) at an oil-water ratio of 10:1-4:1, stir at 400-1200 rpm, and emulsify for 6-18 min; (4) Cross-linking: After emulsification, two cross-linking agents are added at a ratio of 1:1-4 for cross-linking; (5) Washing: Stop stirring and wash with acetone; (6) Centrifugation: Centrifuge in a low-temperature centrifuge and collect the precipitate.

3. The preparation method according to claim 2, characterized in that: The ratio of n-hexane to liquid paraffin in step (1) is 0:1 to 1:0, but does not include 0:

0.

4. The preparation method according to claim 2, characterized in that: The emulsifier in step (1) is one or more of Tween, Span, sorbitan monooleate, sorbitan trioleate, sorbitan tristearate, sorbitan sesquioleate, glycerol ether polymer and polyoxyethylene hydrogenated castor oil.

5. The preparation method according to claim 2, characterized in that: The cross-linking agent in step (4) is one or more of glutaraldehyde, 1,4-butanediol diglycidyl ether, tetrahydroxymethylphosphonium chloride, carbodiimide, epichlorohydrin, sodium metaphosphate, ethylene glycol diglycidyl ether, proanthocyanidins, hesperidin, tannic acid, genipin, riboflavin, naringenin, quercetin, epigallocatechin gallate, oleuropein, L-threose, phytic acid, isocyanate, vanillin, citral, acyl azide, diphenyl phosphate and di(N-hydroxysuccinimide) suberate.

6. The preparation method according to claim 5, characterized in that: The cross-linking agent in step (4) is glutaraldehyde and 1,4-butanediol diglycidyl ether.

7. The preparation method according to claim 2, characterized in that: The low-temperature centrifuge described in step (6) is centrifuged at a speed of 4000 rpm.

8. Use of the collagen-chitosan composite microspheres as claimed in claim 1 in dermatology and tissue engineering.

9. Use of the collagen-chitosan composite microspheres as claimed in claim 1 in medical aesthetic filling materials.

Citation Information

Patent Citations

  • Implant for subcutaneous or intradermal injection

    US6716251B1

Cited By

  • Preparation method of collagen-based microspheres and application of collagen-based microspheres in preparation of subcutaneous tissue filling material

    CN121102579A